Scanning Microscope-Energy Dispersive X-Ray (Sem-Edx) Studies of Quercus infectoria Gall - A, Hasmah; W H, Wan Nurhidayah; H, Hermizi; S, Rapeah (2015)
Quercus infectoria gall extract are popular among Malaysian. Therefore there is vast availability of the galls supply in Malaysian local market. However, these galls found in Malaysian market were brought out from another country such as Iran and India. In this regard, maintaining the quality of the source is very important to ensure the expected health benefit. In this study we used scanning microscope-energy dispersive X-ray (SEM-EDX) to analyse the microscopical image and basic elements present in crude and aqueous extract of Quercus infectoria gall in comparison with macroscopical view. Galls of Q. infectoria were divided into external surface and cross section inner parts were performed using hard cutter. Macroscopical view showed that the gall looked alike ball-shaped with numerous protruding blunt horn-like lumps on external rugae like surface (1.4-2.3 cm in diameter). The cross section revealed three major parts; outer, middle and inner layer containing whitish core separated by barrier. The parenchyma cells could be seen in most part of the layer and elongated to formations of tracheid cells. Elemental analysis showed that the galls contain various useful minerals of carbon, calcium, oxygen, magnesium, silicon, potassium, sodium and chlorine. The elements distributions were different in each part. Most of the elements found in the external surface. The cross section part showed the highest number of elements on the outermost layer and it was the only part where the sodium and chlorine were found. These present study serve as a valuable information about macroscopic and microscopic features of the galls besides trace elements composition that will be useful for the establishment of quality standards and future reference for galls authentication.